Pemanfaatan Musik Klasik sebagai Media Pengelola Kesehatan Mental Gen Z - Hannan, Fathiya; Setiawan, Joe Harrianto (Persatuan Wartawan Indonesia, 2024)
Currently, Generation Z is prone to developing signs of mental health illnesses, such as stress and anxiety. If not managed properly, these symptoms could lower their overall quality of life. In contrast, Gen Z shows traits that are typically characterized by openness, tolerance, and innovation, allowing them to develop creative approaches to the challenges they face. One approach involves utilizing classical music as a means of regulating their mental well-being. The younger generation mostly chooses to engage in the act of listening to classical music due to its character that often associated with music that soothes the soul. The author conducted research to see how classical music fans among Gen Z utilize this type of music as a means of maintaining a good mental state. This study employs the Uses and Gratifications (UGT) theory, which refers to the four typologies of uses outlined in McQuail's UGT theory: distraction, personal relations, personal identity, and monitoring. The method used is a qualitative descriptive research, with semi-structured interviews involving three respondents and document analysis as data gathering approaches. The research findings indicate that classical music is effectively utilized as a means of regulating the mental well-being of listeners. This is evident through the satisfaction of the four typologies of uses mentioned earlier when engaging with classical music. These findings demonstrate the potential of classical music to aid individuals in coping with or controlling their mental health by inducing a state of tranquillity, neutralizing negative emotions, providing a sense of security and comfort with one's identity, and stimulating the mind through imaginative visualizations evoked by the act of listening to classical music.